PkM METODE LATIHAN STRIKER UNTUK MENCETAK GOL PEMAIN SEPAKBOLA UNM. FC - M Said Zainuddin; Awaluddin Awaluddin; Arifuddin Usman; Sudirman Sudirman; Abdul Rahman; Suprianto Suprianto (Program Studi Ilmu Keolahragaan, 2023)
The community service carried out aims to provide forms of training for unm.fc football players regarding forms of training for strikers so they can score goals and do good finishing in front of goal. In this service, not only strikers are given the opportunity to carry out forms of striker training, but also provide opportunities for all players to practice. The results of the service show that the level of understanding and skill of the players in carrying out forms of striker training is quite good, seen from the goals created during the service and the lack of balls far from the target (goal), and the shooting carried out by the players is already directed. and hit the target.